Preserving Malay Islamic Identity and Developing Life Skills through Arab–Malay Calligraphy Pedagogy in Riau Boarding Schools - Achmad Ghozali; Jamaluddin Jamaluddin; Darusman Darusman; Suardi Suardi; Henrizal Hadi (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2026)
The revitalization of Arab–Malay calligraphy in Islamic boarding schools throughout Riau constitutes a strategic initiative to preserve Malay Islamic cultural identity while enhancing students’ life skills in response to contemporary educational and social challenges. This research develops and analyzes an instructional framework for Arab–Malay calligraphy learning that integrates cultural preservation with student competency development. Utilizing a Research and Development (R&D) methodology, the study employed a systematic instructional design process comprising needs analysis, learning design, development, implementation, and evaluation. Data collection involved classroom observations, in-depth interviews with pesantren leaders, calligraphy instructors, and students, as well as documentation of learning facilities, instructional programs, and students’ artworks. Qualitative analysis was conducted using an interactive model of data reduction, data display, and continuous verification. The results demonstrate that the revitalization of Arab–Malay calligraphy is most effective when implemented through an integrated instructional framework that combines formal classroom instruction with workshop-based mentoring. Classroom instruction reinforces foundational competencies such as letter formation, proportion, and writing discipline, while workshops offer intensive opportunities for talent development, creativity, and artistic specialization. Instructional methods based on demonstration, imitation, repetitive practice, and continuous instructor feedback significantly improve students’ technical skills, perseverance, and motivation. In addition to artistic competence, Arab–Malay calligraphy learning fosters creativity, self-reliance, productivity, collaboration, and a heightened sense of pride in Malay Islamic cultural heritage. The study concludes that Arab–Malay calligraphy should be regarded not only as an aesthetic-religious art form but also as a culturally grounded instructional framework that advances life skills education, student empowerment, and the preservation of Malay–Nusantara Islamic traditions within the pesantren context.